Determination of gonosomatic index, hepatosomatic index and condition factor in Liza carinata (Valenciennes, 1836) - Hashim, E. S.; Salman, N. A.; Abdulhassan, J. K. (Iraqi Journal of Aquaculture, 2022)
Morphometric of examination of gonads of Liza carinata were performed for one year (October 1995 – September 1996) to study the maturation development. Monthly variation in gonado – somatic index (GSI) were noticed, that started with low values during October and November. Significant increase in (GSI) was recorded during the period December - April with the peak in February (3.59 in males & 9.33 in females) followed by a significant decline during May – September. Variations in hepato – somatic index (HSI) were related to feeding activity rather than gonadal maturation. Peaks of HIS & GSI were recorded at similar time period. On the contrary, the somatic condition factor (SCF) was closely related to gonadal maturation stages. Lower values (SCF) were recorded during winter months which showed higher values in GSI.